"Functional Fashions for the Physically Handicapped": Disability and Dress in Postwar America. (3rd July 2022) - Wright, Natalie E.
Abstract : In this essay, I argue that clothing played an important role in the establishment and maintenance of the postwar American project of independence and "normalcy." Using previously unpublished sources, I trace the history of Functional Fashions, a clothing line of accessible garments for disabled persons in the United States that existed from 1958 to 1976. Designer Helen Cookman created the line as well as the associated non-profit Clothing Research and Development Foundation (CRDF). This essay establishes a history of both the Functional Fashions line and the CRDF, including Cookman's design methodology behind the garments, how CRDF partnered with other important sportswear designers, and how they created the ideal Functional Fashions user. I ultimately show that the goal of the line was for Functional Fashions users to participate in the postwar American culture of bodily autonomy and that CRDF leadership framed this participation as a form of psychological rehabilitation.